Book of abstracts of the 2nd International Scientific Conference "Teaching Methods for Economics and Business Sciences", 7. May 2018, Maribor, Slovenia - Marina Bajić; Gajšt, Nataša (2018)
Today’s global business environment is faced with complex and multidisciplinary issues. As business schools educate new generations of business people who will need to deal with these issues, the teachers at these institutions need to constantly innovate their teaching methods and approaches in order to pass relevant knowledge about business practices, processes and environments to their students. New, innovative approaches to teaching economics- and business-related subjects are thus essential to spark our students' curiosity and innovativeness and to develop their professional competences and skills so that our graduates, once employed, will have a positive impact of business as well as on society. This book presents the abstracts of the 2nd International Scientific Conference »Teaching Methods for Economics and Business Sciences« held on 7 May 2018 at the University of Maribor, Faculty of Economics and Business. I would like to express my thanks to all authors who submitted their work for this conference in our common search for the answer to the above question.
Keywords: higher education; teaching practice; teaching methods; economics and business studies; students